COMPETITIONS INVOLVING ART SCHOOL STUDENTS: PURPOSE, OUTCOMES, AND MOTIVATION - Abdurayimov Faxriddin Muxammadali o‘g‘li (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
This article explores the role of competitions in the artistic and personal development of students in art schools. It examines the objectives behind organizing such contests, their impact on students' skills, confidence, and creativity, and how they serve as a source of motivation. The paper also discusses how competitive environments contribute to self-expression, peer learning, and the recognition of talent in the field of music, visual arts, and performing arts education.